Effects of La Dopant on Nanocluster Size and Optical Band Gap of CdO Films Prepared by Sol-Gel Method - Alahmed, Z. A.; Serbetci, Z.; Yakuphanoğlu, Fahrettin (Polish Acad Sciences Inst Physics, 2013)
The undoped and lanthanum doped cadmium oxide thin films were prepared by sol-gel method. The CdO films were doped with various percentages of La, 0.1, 0.5, 1, and 2 at.%. We have investigated the structural properties of the CdO films by atomic force microscopy. The obtained results show that both the grain size and the surface roughness of CdO films reduce with increase of La doping content. Additionally, the result shows a significant decrease of the transmittance in the range of 300 to 500 nm with increase of La doping level. The optical band gap of CdO films increases with La doped CdO films. It was found that the band gaps to be 2.25, 2.36, 2.4, 2.28, and 2.31 eV for La contents with 0.1, 0.5, 1, and 2 at.% doped CdO, respectively.
Keywords: Thin-Films; Cadmium-Oxide